2020
DOI: 10.1080/15384101.2020.1749472
|View full text |Cite
|
Sign up to set email alerts
|

Overexpressed microRNA-494 represses RIPK1 to attenuate hippocampal neuron injury in epilepsy rats by inactivating the NF-κB signaling pathway

Abstract: Objective: The effects of microRNAs (miRNAs) have been identified in epilepsy (Ep) in recent years, our research was focused on the functions of miR-494 in Ep and its inner mechanisms. Methods: The Ep modeled rats induced by lithium chloride-pilocarpine were treated with agomir-miR-494 or RIPK1-siRNA. The pathology of rat hippocampal tissues was observed. Expression of miR-494, receptor-interacting protein kinase 1 (RIPK1) and nuclear factor-kappaB (NF-κB) p65 was assessed by RT-qPCR and Western blot analysis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 35 publications
(39 reference statements)
0
6
0
1
Order By: Relevance
“…Losmapimod was shown to exert protective effects on epilepsy by reducing neuron loss through the suppression of MAPK phosphorylation. Qi et al ( 31 ) demonstrated that miR-494 inhibits receptor-interacting serine/threonine-protein kinase 1 to suppress the apoptosis of hippocampal neurons and reduce the neuronal damage in epileptic rats by deactivating the NF-κB pathway. In addition, it has been reported that rehmannioside A attenuates depression by suppressing ER stress and apoptosis in the hippocampus of chronic unpredictable mild stress-induced rats by regulating MAPK signaling ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Losmapimod was shown to exert protective effects on epilepsy by reducing neuron loss through the suppression of MAPK phosphorylation. Qi et al ( 31 ) demonstrated that miR-494 inhibits receptor-interacting serine/threonine-protein kinase 1 to suppress the apoptosis of hippocampal neurons and reduce the neuronal damage in epileptic rats by deactivating the NF-κB pathway. In addition, it has been reported that rehmannioside A attenuates depression by suppressing ER stress and apoptosis in the hippocampus of chronic unpredictable mild stress-induced rats by regulating MAPK signaling ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interleukin-27 upregulates miR-6852-5p and causes necrosis in cervical cancer cells by inhibiting Forkhead box protein M1 (FOXM1) expression [ 76 ], with the FOXM1 being suppressed by FOXO3a [ 138 ]. Upregulated miR-494-3p inhibits the expression of receptor-interacting serine/threonine-protein kinase 1 (RIPK1) in epilepsy rats [ 139 ], which is a necroptosis regulator [ 140 ]. Moreover, miR-494-3p targets the c-Myc and SIRT1 genes in ovarian cancer (OVCAR3) cells [ 87 ].…”
Section: Relationship Between Mirna Akt Effectors and Cell Functionsmentioning
confidence: 99%
“…Підтвердженням цього припущення є дані щодо нейропротекторного ефекту інактивації клітин мікроглії та інгібування NF-kB на моделі генералізованої епілепсії, спричиненої каїновою кислотою [13]. Надмірна експресія мікроРНК, яка інактивує сигнальний шлях NF-kB, зменшує пошкодження нейронів гіпокампу при епілепсії, зменшує реакцію активації мікроглії [14].…”
Section: рівень Tnf-α та P-nf-kb в дорсальному гіпокампіunclassified